The Myths of Textualism and Their Relevance To the ALI’s Restatement of the Law, Copyright - Newman, Jon O. (The Columbia Journal of Law & the Arts, 2021)
In 2015, Justice Elena Kagan famously proclaimed, “We’re all textualists now.” To which I ask, “When were we not?” Justice Kagan not only used the word “now,” but also provided her evidence that being a textualist is of recent vintage. She asserted that when she was at the Harvard Law School in 1983, the inquiry concerning a statute was “what should this statute be,” rather than what do “the words on the paper say.” And she attributed this inquiry to a “policy-oriented” approach with judges “pretending to be congressmen.” With respect, I cannot credit this evidence. I started my law school years thirty years earlier at Yale Law School, which reveled in its reputation for being concerned with “policy,” yet I never once heard a professor suggest that the text of a statute should be ignored in favor of a “policy” interpretation. “Policy” was thought relevant when a statutory provision was unclear, or, in nonstatutory cases, when existing case law provided no clear answer. Of course, even in a statutory case, the policy to be implemented was the policy preferred by Congress, not by judges. I take on the task of refuting Justice Kagan because I believe the “now” in her statement is only one of many myths about textualism, myths often perpetuated by some judges, legal scholars, and politicians, especially when they disagree with a court’s decision. Refuting these myths is particularly relevant to the current controversy within the American Law Institute concerning the effort to craft a Restatement of the Law, Copyright.